Collaborative Governance in Supporting the Anti-Corruption Village Program Through ETIKA (Anti-Gratification Showcase) in Kauman Village, Bojonegoro - Dhea Agustina; Ahmad Taufiq; Ida Swasanti (Universitas Lambung Mangkurat, 2026)
The practice of gratification at the village level remains a serious problem because it is often considered part of social customs in public services, making it challenging to eradicate. This study aims to understand how the implementation of Collaborative Governance supports the Anti-Corruption Village Program through the ETIKA (Anti-Gratification Showcase) innovation in Kauman Village, Bojonegoro Regency. This study uses a descriptive qualitative approach, drawing on the Collaborative Governance theory of Ansell and Gash (2008), which covers four main aspects: initial conditions, institutional Design, facilitative leadership, and collaboration processes. Data collection was conducted through in-depth interviews, participatory observation, and documentation, using a purposive sampling technique that included the village government, the Inspectorate, schools, the Village Consultative Body (BPD), the Media, and the community. The results of the study indicate that the implementation of Collaborative Governance through the ETIKA innovation is effective, as seen from increased transparency, accountability, and community participation in preventing gratification. However, challenges persist due to limited understanding among some communities of the dangers of gratification and its reporting mechanisms. ETIKA’s innovation has been proven to strengthen the culture of integrity and collaboration among stakeholders towards clean, integrated village governance.